Slavs but not Slaves: Slav Migrations to Southern Italy in the Early and High Middle Ages - Nikolić Jakus, Zrinka (2010)
The presence of Slavs on western Adriatic coast can be ascertained quite soon after the settlement on the eastern shore, although the sources speak only of isolated war campaigns. Nevertheless, toponomastic and onomastic traces indicate the presence of Slavs in a wider area of South Italy, and for the beginning of the eleventh century we can even talk of organized colonization (most likely of the Narentan Slavs) at Gargano, which resulted in at least two castella – Devia and Peschici – with a predominantly Slavic population, governed by a župan. Their self-government ended with the arrival of the Normans in 1054, which probably contributed to the already ongoing assimilation.
Projekt MZOS
ENG